Arhytmogenic Right Ventricular Displasia and Sudden Young Adult Deaths - Gülmen, Mete Korkut; Salaçin, Serpil; Tuncer, İlhan (The Bulletin of Legal Medicine, 1997)
Forensic Medicine specialists often has to deal with sudden-unexpected deaths. Arhytmogenic Right Ventricular Displasia (ARVD) had been defined in 1961, yet previously took place in the textbooks. It is claimed that, this antity is responsible from the sudden deaths of the young adults and athletes. Some of the authors assert that it can be defined not only clinically but also morphologically. Our two different serials revealed that, the criterias which are defined as patognomonic morphology, should be crossed over again in large serials, since these findings are common in randomly selected violent deaths also. In this paper, the findings of the two previous studies are summarized and the proposed morphological criterias of ARVD are criticized. Key words: ARVD, Autopsy, Medico-legal, Sudden Death, Cardiac Pathology, Right Ventricle.